Anxiety and attitudes towards illness in patients with ovarian tumours and uterine fibroids - Pawłowska, Beata Pawłowska; Międlar, Krzysztof; Biały-Międlar, Karolina; Dziurzyńska, Ewa (Current Problems of Psychiatry, 2012)
The object of the study was to answer the question: do any dependencies occur, if any, between the anxiety level and attitudes towards their illness in patients with ovarian tumours and uterine fibroids qualified for surgical treatment? The examined group consisted of 60 patients qualified for surgery due to benign ovarian tumours (30 women) and uterine fibroids (30 women). The average age of patients was 40 years. Methods. In the research the R.Cattell’s IPAT Anxiety Scale-Self-Analysis Form was used as well as the Questionnaire Examining Attitudes to Illness by B. Pawłowska. Results and conclusions. Based on the results achieved in the study the following conclusions were formulated: High level of general anxiety in patents coexists with reacting with the sense of depression and sorrow and blaming the fate while ill. High level of hidden anxiety in patients is combined with reacting with the sense of helplessness while ill and treating their illness as an obstacle to accomplishing goals. High level of manifest anxiety is combined with treating the illness as a “punishment for sins”, lack of self-acceptance as a sick person, sense that the illness makes interpersonal relations more difficult, concentration on the symptoms of the illness and with a sense of sadness.